A STUDY ON STUDENTS’ PERCEPTION TOWARD ENGLISH LEARNING AT SMP KATOLIK ST. THERESIA TANAWANGKO - Desy Fransiska Ansow; Sanerita T. Olii; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
In Indonesian, English has been decided as a first foreign language by the national education which can be learned started from elementary school up to university level, but there are some students who are not interested in learning English. One way to find out the reasons for students’ disinterest in English learning arises from the data is from their own perceptions. The purpose of this study was to describe students’ perceptions/opinions on English learning in SMP Katolik St. Theresia Tanawangko. Since it dealt with students’ perceptions/opinions, this study was categorized as a survey research. The sample of this study was ninth students at SMP Katolik St. Theresia Tanawangko in the academic year 2019-2020. Since students’ perceptions were the focus of this survey, the data were collected using a questionnaire. It focused on four indicators and the questionnaire itself consisted of 20 items with 5 items per indicator. Result of the data analysis leads the researcher to arrive at the following conclusions: (1) majority of the sampling students (87%) had positive attitudes toward English learning, (2) 90% were strongly motivated to learn English or love learning English, and (3) 93% learn English because it is a compulsory subject. They learned the language for the following purposes: to have internet access (89%), get job in the future (95%), and widen their knowledge of the world (91%). After knowing students’ perceptions, it is important for English teacher to further increase motivation and foster a sense of courage in students at school, especially in English learning.